Indium-Catalyzed Friedel–Crafts Alkylation of Monosubstituted Benzenes by 1-Bromoadamantane - Mosset, Paul; Grée, René (Synlett, 2013)
Indium salts such as InCl3 and InBr3 (ca. 1–5 mol%) efficiently catalyzed the Friedel–Crafts reaction of 1-bromoadamantane with benzene and monosubstituted benzenes to give 1-adamantyl benzenes. Indium bromide enabled faster reactions than indium chloride but the latter was more suitable in the case of halobenzenes.
Keywords: adamantanes; alkylation; catalysis; indium; Lewis acids